2015
DOI: 10.1007/s10067-015-3073-0
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA in the influenza vaccine may have contributed to the development of ANCA-associated vasculitis in a patient following immunisation

Abstract: A number of large studies have demonstrated influenza vaccinations to be safe and effective. However, there have been some sporadic case reports, describing a temporal association of influenza vaccination with onset or relapse of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis. The nature of this association, beyond time of occurrence, remains unknown. The presentation of a previously healthy patient who developed ANCA-associated vasculitis (AAV) shortly after influenza vaccination provided u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…In one patient with antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis arising after influenza vaccination, a careful study of the patient's peripheral blood mononuclear cells in vitro demonstrated the production of pathogenic anti-proteinase 3 autoantibodies upon stimulation with influenza vaccines containing viral RNA (49). This finding supports the hypothesis that influenza vaccine, similarly to influenza infection, may trigger autoantibody production and consequent vasculitis by acting on innate immunity via Toll-like receptor 7 that binds viral RNA.…”
Section: Systemic (Autoimmune) Vasculitissupporting
confidence: 72%
“…In one patient with antineutrophil cytoplasmic antibodies (ANCA)-associated vasculitis arising after influenza vaccination, a careful study of the patient's peripheral blood mononuclear cells in vitro demonstrated the production of pathogenic anti-proteinase 3 autoantibodies upon stimulation with influenza vaccines containing viral RNA (49). This finding supports the hypothesis that influenza vaccine, similarly to influenza infection, may trigger autoantibody production and consequent vasculitis by acting on innate immunity via Toll-like receptor 7 that binds viral RNA.…”
Section: Systemic (Autoimmune) Vasculitissupporting
confidence: 72%
“…This is an interesting and important topic for further exploration. Endogenous TLR7 ligands include mainly ssRNA such as those from viral infections 7981 , or even single nucleotide such as guanosine (G)/2′-deoxyguanosine (dG) 82 . Such nucleotide(s) in atherosclerotic lesions may activate TLR7 and promote atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the patient showed overlapping sets of clinical features it was difficult to diagnose the exact subtype of AAV [ 10 , 11 ]. Currently, a handful of AAV cases have been reported in temporal association with influenza vaccination [ 12 17 ]. Recently, The Brighton Collaboration Vasculitis Working Group published a systematic literature review on adverse events following immunization (AEFI) suggesting an association between influenza vaccination and vasculitis, however no evidence is found to confirm this association yet [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the ASIA criteria defined by Alijotas-Reig, our patient met three major criteria, including exposure to an external stimulus, minimum latency time of days and muscle weakness [ 28 ]. Recently, another possible mechanism has been proposed regarding influenza vaccines containing viral RNA which may increase the production of Proteinase 3 (PR3-ANCA) and thus further contribute to the development of AAV following influenza vaccination [ 17 ].…”
Section: Discussionmentioning
confidence: 99%